Intake of phthalate-tainted foods and microalbuminuria in children: The 2011 Taiwan food scandal. (April 2016) - Tsai, Hui-Ju; Chen, Bai-Hsiun; Wu, Chia-Fang; Wang, Shu-Li; Huang, Po-Chin; Tsai, Yi-Chun; Chen, Mei-Lien; Ho, Chi-Kung; Hsiung, Chao A.; Wu, Ming-Tsang
Abstract: Background: A major threat to public health involving phthalate-tainted foodstuffs occurred in Taiwan in 2011. Phthalates, mainly di-(2-ethylhexyl) phthalate (DEHP), were intentionally added to several categories of food commonly consumed by children. This study investigated the relationship between intake of the phthalate-tainted foods and renal function in children. Methods: Children aged ≤ 10 years with possible phthalate exposure were enrolled in this study between August 2012 and January 2013. Questionnaires were used to collect details of exposure to phthalate-tainted foodstuffs, and blood and urine samples were collected for clinical biochemical workup. The clinical biomarkers of renal injury, including urinary microalbumin, N-acetyl-beta-d -glucosaminidase (NAG), and β2-microglobulin were measured. Exposure was categorized based on recommended tolerable daily intake level defined by the U.S. Environmental Protection Agency (0.02 mg/kg/day) and the European Food Safety Authority (0.05 mg/kg/day). Results: We analyzed intake and renal function of 184 children whose intake of DEHP-tainted foods was known. Higher DEHP exposure to DEHP-tainted foods was significantly associated with increase of urine albumin/creatinine ratio (ACR). Children in the high-exposed group (daily DEHP intake (DDI) > 0.05 mg/kg/day) had 10.395 times the risk of microalbuminuria than the low-exposed group (DDI ≤ 0.02 and > 0 mg/kg/day) and no-exposed group combined after adjustment (95% CI = 1.096–98.580, P = 0.04). Conclusion: Intake of DEHP from phthalate-tainted foods may be a potential risk factor for microalbuminuria, a marker of glomerular injury in children. Highlights: A major health threat from phthalate-tainted foodstuffs occurred in Taiwan in 2011. DEHP-tainted food intake increases the excretion of urinary ACR in children. DEHP-tainted food intake may increase the risk of microalbuminuria.